APLIKASI TEMATIS METODE MAWDU’I HADIS TENTANG ORANG-ORANG MUKMIN LAKSANA SATU BANGUNAN - Muhammad Qomarullah (UIN Siber Syekh Nurjati Cirebon, 2021)
The author will increase the theme of hadiths related to traditions related to one believer and another brother. This research requires a deep understanding using a variety of approaches, both textually, intertextually, and contextually. Not all traditions are valid from the Messenger of Allah (qat'i al-wurud), so takhrij al-Hadith (proof of fidelity) is needed. Mawdu'i method could be relied upon to solve problems that exist in society, because this method provides an opportunity for someone to try to provide answers to problems taken from the instructions of the Qur'an and Hadith. The application of this method is by determining the hadiths related to